The uptake and release of cationic surfactant from polyampholyte microgel particles in dispersion and as an adsorbed monolayer - Bradley, Melanie (Langmuir : the ACS journal of surfaces and colloids, 2009)
The use of novel polyampholyte microgel particles for the controlled absorption and release of a cationic surfactant has been investigated. The addition of cetylpyridinium chloride (CPC) to aqueous dispersions of poly(2-diethylamino)ethyl methacrylate-co-methacrylic acid (DEAEM-co-MAAc) microgel particles has been studied with respect to CPC concentration and solution pH. CPC was found to absorb into the polyampholyte microgel particles, resulting in reduced hydrodynamic diameter and electrophoretic mobility, when added to microgel dispersion at pH 11. Strong desorption could be induced by switching the pH from 11 to 3, with most of the desorption occurring in the region of the isoelectric pH of the particles. The properties of surface-adsorbed monolayers of polyampholyte microgel particles were also investigated, both in the presence and absence of CPC. The substrate surface charge was found to influence the swelling profile of the adsorbed microgel monolayers. The interaction of CPC surfactant with monolayers of adsorbed microgel particles shows strong correlations with the interaction of CPC surfactant with microgel particles in dispersion